Online Transactions (E-Commerce) In The Covid-19 Pandemic Period Viewed From Positive Laws In Indonesia - Ahmad Rosidi; M. Zainuddin; Masyhur; Lalu Muhammad Faisal; Muhammad Saleh (CV. Inara, 2021)
The business concept in the digital era is now changing all lines from offline buying and selling transactions to online buying and selling transactions. Through this business concept, the existence of the internet or e-commerce only makes buying and selling transactions or legal relationships that occur shorter, easier and simpler. An agreement in the e-commerce transaction takes place, will relate to the parties who make the transaction. The purpose of this study is to find out how buying and selling online transactions on online websites, such as Bukala, Bukalapak, Shopee, Facebook, WahatsApp. etc. during the covid 19 pandemic and to find out the positive and negative impacts that arise in online buying and selling transactions according to business concepts in the economy. Digital banking and e-banking are bank products that are currently in great demand by the public. Especially in the midst of this COVID-19 pandemic. The PSBB policy issued by the government has limited physical economic activity. This makes many people who want to carry out economic activities that on average depend a lot on banks, being unable to do it smoothly. In general, people make buying and selling transactions by meeting directly between the seller and the buyer, and even before the existence of currency as a means of payment, buying and selling transactions were carried out by bartering or exchanging goods between people who needed the goods with each other. Along with the times, new technologies began to emerge that make it easier for someone to do their work. One such technology is the Internet. The internet has brought changes to human activities in an effort to fulfill all their needs, because the internet can open up a world that is so wide and is able to provide various information and facilities needed. The method used in the research uses normative research, namely a library research by examining library materials related to the object under study. This study uses a statutory approach and a case approach. The analysis used is in the form of qualitative analysis, namely data analysis by providing a description of the findings to answer the problems that occur. One of the facilities provided by internet media is buying and selling activities through electronic media or commonly called E-commerce. E-commerce is mostly done by anyone, especially the modern business community because it is felt that it can streamline time, so that someone can transact with anyone and at any time without meeting face to face or know each other in trade. They only base buying and selling transactions on mutual trust, so that the sale and purchase agreements that occur between the parties are also carried out electronically, therefore there is no agreement file as in conventional buying and selling transactions. Although there are conveniences provided by e-commerce, it turns out that there is also a factor that hinders the implementation of e-commerce which turns out to be problematic for the implementation of e-commerce itself. One of them is the seller's responsibility if he defaults in buying and selling through e-commerce.